Automatic protection system for slow rate events in power systems - Gheitasi, A.; Moghavvemi, M.; Omar, R. (2009)
Motor current signature analysis is defined as a strategy to diagnose the motors significant events by locating a set of frequency components using pattern recognition. However there is no index to give a clear idea about the fault extension and advise the deadline time and protection action on the situation. In this paper a new definition for protection levels based on dynamic of faults is presented. Here the main point is to have a clear alert for the system operators and buy a proper time to do the corrective action before a hazardous failure going to be unreturnable.